An Electrolyte for Reversible Cycling of Sodium Metal and Intercalation Compounds. Issue 2 (20th December 2016) - Schafzahl, Lukas; Hanzu, Ilie; Wilkening, Martin; Freunberger, Stefan A.
Abstract: Na battery chemistries show poor passivation behavior of low voltage Na storage compounds and Na metal with organic carbonate‐based electrolytes adopted from Li‐ion batteries. Therefore, a suitable electrolyte remains a major challenge for establishing Na batteries. Here we report highly concentrated sodium bis(fluorosulfonyl)imide (NaFSI) in dimethoxyethane (DME) electrolytes and investigate them for Na metal and hard carbon anodes and intercalation cathodes. For a DME/NaFSI ratio of 2, a stable passivation of anode materials was found owing to the formation of a stable solid electrolyte interface, which was characterized spectroscopically. This permitted non‐dentritic Na metal cycling with approximately 98 % coulombic efficiency as shown for up to 300 cycles. The NaFSI/DME electrolyte may enable Na‐metal anodes and allows for more reliable assessment of electrode materials in Na‐ion half‐cells, as is demonstrated by comparing half‐cell cycling of hard carbon anodes and Na3 V2 (PO4 )3 cathodes with a widely used carbonate and the NaFSI/DME electrolyte. Abstract : Enabling electrolyte : A highly concentrated sodium bis(fluorosulfonyl)imide (NaFSI) in dimethoxyethane (DME) electrolyte is shown to stably passivate low voltage sodium anodes and allow for stable cycling of sodium metal as well as sodium intercalation compounds. The NaFSI/DME electrolyte may enable Na‐metal anodes and allows for more reliable assessment of electrode materials in Na‐ion half‐cells.